2022
DOI: 10.3390/plants11070988
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tolerance to Lanthanum and Cerium in Helianthus Annuus Plant: Effect on Growth, Mineral Nutrition, and Secondary Metabolism

Abstract: Rare earth elements (REEs) present a group of nonessential metals for the growth and development of plants. At high concentrations, they can induce internal stress and disturb the physiological and biochemical mechanisms in plants. The potential uptake of lanthanum (La) and cerium (Ce) by the horticultural plant Helianthus annuus and the effect of these elements on its growth, its absorption of macroelements, and the contents of phenolic compounds and flavonoids were assessed. The plants were exposed to 0, 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In conformity, the polyphenol contents were stimulated after the exposure of the okra plants to increasing doses of Al and Ba. This behavior was also observed in Brassica juncea and Cackile maritima plants subjected to Ba stress [ 19 ], as well as in Helianthus annuus plants treated with La and Ce [ 63 ]. Indeed, phenolic compounds play the role of antioxidants by participating in ROS scavenging, catalyzing the reactions of oxygenation through the formation of metallic complexes, and via the inhibition of the activities of oxidizing enzymes [ 64 ].…”
Section: Discussionmentioning
confidence: 67%
“…In conformity, the polyphenol contents were stimulated after the exposure of the okra plants to increasing doses of Al and Ba. This behavior was also observed in Brassica juncea and Cackile maritima plants subjected to Ba stress [ 19 ], as well as in Helianthus annuus plants treated with La and Ce [ 63 ]. Indeed, phenolic compounds play the role of antioxidants by participating in ROS scavenging, catalyzing the reactions of oxygenation through the formation of metallic complexes, and via the inhibition of the activities of oxidizing enzymes [ 64 ].…”
Section: Discussionmentioning
confidence: 67%
“…[54]. In addition, Dridi et al (2022) demonstrated that La contents in Helianthus annuus roots were greater than those in shoots [55].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of La on the biosynthesis of secondary metabolites was reported in the literature. Dridi et al (2022) exposed Helianthus annuus plants to La (1-10 µM) and discovered that the presence of La promoted the production of phenols and flavonoids [55]. In addition, La stimulated taxol production in Taxus yunnanensis cell cultures [10] and induced a general increase in certain phenolic acids in Hypericum perforatum [74].…”
Section: Discussionmentioning
confidence: 99%
“…REE tolerance mechanisms have been reported in plants such as Dicranopteris linearis, Phytolacca sp., Helianthus Annuus [32][33][34], and in microalgae such as Galdieria sulphuraria and Desmodesmus quadricauda [35,36], but very little information concerns diatoms [26].…”
Section: Discussionmentioning
confidence: 99%